EXOSC10/Rrp6 is post-translationally regulated in male germ cells and controls the onset of spermatogenesis. Issue 1 (December 2017) - Jamin, Soazik; Petit, Fabrice; Kervarrec, Christine; Smagulova, Fatima; Illner, Doris; Scherthan, Harry; Primig, Michael
Abstract EXOSC10 is a catalytic subunit of the exosome that processes biologically active transcripts, degrades aberrant mRNAs and targets certain long non-coding RNAs (lncRNAs). The yeast orthologue Rrp6 is required for efficient growth and gametogenesis, and becomes unstable during meiosis. However, nothing is known about the localization, stability and function of EXOSC10 in the rodent male germline. We detect the protein in nucleoli and the cytoplasm of mitotic and meiotic germ cells, and find that it transiently associates with the XY body, a structure targeted by meiotic sex chromosome inactivation (MSCI). Finally, EXOSC10 becomes unstable at later stages of gamete development. To determineExosc10 's meiotic function, we inactivated the gene specifically in male germ cells using cre recombinase controlled byStra8 orDdx4 /Vasa promoters. Mutant mice have small testes, show impaired germ cell differentiation and are subfertile. Our results demonstrate that EXOSC10 is post-translationally regulated in germ cells, associate the protein with epigenetic chromosome silencing, and reveal its essential role in germ cell growth and development.